Endoscopic transpapillary stent placement in patients with necrotizing pancreatitis and disconnected main pancreatic duct syndrome - Shabunin, Aleksey V.; Bagatelia, Zurab A.; Bedin, Vladimir V.; Korzheva, Irina Yu; Shikov, Dmitry V.; Kolotilshchikov, Andrei A.; Kalashnikova, Elena A.; Covantsev, Serghei (Frontiers in Surgery, 2023)
Introduction. Pancreatic necrosis is one of the most severe acute abdominal conditions, accounting for 15-20% of all patients with acute pancreatitis and characterized by significant rates of postoperative complications and mortality. Patients with pancreatic necrosis, in which pathological changes are localized in the proximal pancreas and retroperitoneal space, deserve special attention. This form of the disease includes patients with disconnected main pancreatic duct (MPD) syndrome that have difficult prognosis.Aim. Improvement of treatment results in patients with necrotizing pancreatitis and signs of the dissociation of the pancreas duct system by using method of endoscopic transpapillary stent placement.The study is designed as a retrospective cohort study. There were 32 patients with acute necrotizing pancreatitis, which have been managed by using the method of endoscopic transpapillary stent placement throughout 2019-2021. Disconnected MPD syndrome was diagnosed in all 32 patients. Twenty-six patients were admitted to the hospital in the first 72 hours, while 6 patients after 72 hours. We have diagnosed necrotizing process located in proximal and central area of pancreas and peripancreatic space in all these patients («Model III»).Positive results related to transpapillary stent placement were noted in 24 patients (75% first cohort). Twenty patients from this group were admitted into hospital in first 48 hours, 4 patientslater than 72 hours from the disease onset. Eight patients (25%second cohort) were failed to succeed in transpapillary stent placement. Complications in the first cohort occurred in 3 patients (12,5%): in one casethe dislocation of stent into duodenum and 2 patients with bleeding after papillosphincterotomy, infected necrotized pancreatitis developed in 5 patients.Mortality observed in 1 case (5%). Complications among the second cohort occurred in 2 patients (25%)erosive bleeding (after debridement), infected necrotized pancreatitis developed in 4 patients. Mortality was observed in 2 cases (25%).Conclusions. Endoscopic transpapillary stent placement is an effective minimally invasive approach in management of patients with necrotizing pancreatitis.